Prehistoric Pottery Production And Technology At Bukit Tengkorak, Sabah, Malaysia. - Chia, Stephen

(untitled)
Bukit Tengkorak ("Skull Hill") is a Neolithic site, located at the top of a hill overlooking the Sulawesi sea and approximately 5 kilometers from Semporna in Sabah, Malaysia (Map 13.1). Archaeological research at Bukit Tengkorak was undertake n in 1994 and 1995 by a joint research team from the Centre for Archaeological Research Malaysia and Muzium Sabah.